Effect of reprocessing and excipient characteristics on ibuprofen tablet properties (2015)
ABSTRACT: Purpose: To determine excipient and ibuprofen:excipient mixture sensitivity to reprocessing produced by either direct compression or wet granulation. Methods: The effect of excipient type, technology and reprocessing on flow, compressibility and compactibility was assessed using and 8x2x2 factorial design. Design Expert® v.8.01 software was employed for data analysis. Pure excipients were processed by direct compression, while the ibuprofen:excipient mixtures were processed by wet granulation. Once compacts were produced, they were milled and reprocessed using the same technologies, respectively. Excipient properties such as particle size, porosity and densities were also evaluated. Results: For most excipients, reprocessing caused a 20 – 50 % decrease in particle size and 5 – 80 % reduction in porosity, but increased compactibility (10 – 50 %). Flow decreased (30 – 50 %) only for highly densified excipients such as calcium carbonate and calcium diphosphate. Conclusion: Microcrystalline cellulose and sorbitol are the excipients with the best tableting properties when reprocessing is conducted via wet granulation and direct compression platforms, respectively.